Synthesis of electron-rich, planarized silicon(IV) species and a theoretical analysis of dimerizing aminosilanes - Kramer, Nina; Jöst, Christoph; Mackenroth, Alexandra; Greb, Lutz (Chemistry - a European journal, 2017)
Equipping silicon(IV) with electron-rich, geometrically constrained NNN- and ONO-tridentate substituents leads to aminosilanes with increased Lewis acidity—expressed through the formation of Si2N2 rings by head-to-tail dimerization. Depending on the substituents, the dimerization can be controlled for the first time, yielding monomeric, structurally reversible and dimeric states. The monomeric species display substantial distortions from tetrahedral towards planar geometry at silicon. The dimerization and the Lewis acidity of aminosilanes are rationalized by (conceptual) DFT, NBO, ETS-NOCV and QTAIM methods. The preorganization at silicon, London dispersion between the substituents and resonance phenomena inside the formed Si2N2 tetracycles are identified as driving forces for the dimerization. Comparison with selected aminosilanes permits general conclusions to be reached on the Lewis acidity of silicon species and on the aggregation of amphiphilic compounds.